Total alkaloids of Corydalis saxicola Bunting ameliorate ulcerative colitis through regulation of metabolite networks and gut microbiota - Jin, Shuyi; Cheng, Xinyi; Han, Feng; Li, Qien; Shang, Jing; Xie, Guoyong; Qin, Minjian (Frontiers in Pharmacology, 2025)
BackgroundYanhuanglian (YHL), derived from the dried herb of Corydalis saxicola Bunting, can inhibit diarrhea and alleviate bleeding in traditional Chinese medicine. YHL is used to treat dysentery and hematochezia, which are recognized as ulcerative colitis (UC) in traditional Chinese medicine. However, the effectiveness and mechanisms of YHL treating UC remain largely unknown. This study aimed to reveal anti-colitis effect and mechanisms of YHL’s total alkaloids (YTA) against UC.MethodsThree graded doses of YTA were introduced to DSS-induced colitis mice for 7 days to evaluate the anti-colitis effect. Colon, serum, and fecal untargeted metabolomics were applicated to analyze the differential metabolites. 16S rRNA sequencing was used to analyze changes in the gut bacteria, while gut microbiota depletion and fecal microbiota transplantation further verified the effects of gut microbiota. Lactobacillus spp. isolated from the mice feces were screened based on the enrichment abundance of YTA in vivo and in vitro, and the therapeutic effect of Lactobacillus johnsonii enriched with YTA was evaluated in colitis mice.ResultsYTA alleviated weight loss, diarrhea, and hematochezia in colitis mice, reducing inflammation and oxidative stress while restoring intestinal barrier impairment. Untargeted metabolomics profiling of colon, serum, and feces demonstrated that YTA restored the disrupted metabolite profiles, with linoleic acid consistently identified as a key differential metabolite. Through the pathway enrichment, linoleic acid metabolism pathway was highlighted. YTA also ameliorated imbalance of the gut microbiota by significantly increasing the abundance of Lactobacillus. Gut microbiota depletion and fecal microbiota transplantation confirmed that the benefits of YTA depended on the presence of gut microbiota. Furthermore, Lactobacillus johnsonii enriched by YTA protected colitis mice against UC.ConclusionYTA exhibited potential anti-colitis activity by modulating metabolomic profiles and the gut microbiota, suggesting its potential as a complementary and alternative therapy in phytomedicine.